2015
DOI: 10.3758/s13414-015-0945-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender identification from high-pass filtered vowel segments: The use of high-frequency energy

Abstract: The purpose of this study was to examine the use of high-frequency information for making gender identity judgments from high-pass filtered vowel segments produced by adult speakers. Specifically, the effect of removing lowerfrequency spectral detail (i.e., F3 and below) from vowel segments via high-pass filtering was evaluated. Thirty listeners (ages 18-35) with normal hearing participated in the experiment. A within-subjects design was used to measure gender identification for six 250-ms vowel segments (/ae/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These results are expected and coincide with behavioral findings reported by Monson et al (2014), who found approximately 92% accuracy among listeners with normal hearing when judging speaker gender from sentences high-pass filtered near 5.7 kHz. Donai and Lass (2015) reported correct gender identification near 85% for 250-ms vowel segments highpass filtered at 3.5 kHz. Taken together, the previous behavioral results and current classification findings support information related to talker sex present in the highfrequency portion of the speech spectrum.…”
Section: B Talker Sex Classificationmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are expected and coincide with behavioral findings reported by Monson et al (2014), who found approximately 92% accuracy among listeners with normal hearing when judging speaker gender from sentences high-pass filtered near 5.7 kHz. Donai and Lass (2015) reported correct gender identification near 85% for 250-ms vowel segments highpass filtered at 3.5 kHz. Taken together, the previous behavioral results and current classification findings support information related to talker sex present in the highfrequency portion of the speech spectrum.…”
Section: B Talker Sex Classificationmentioning
confidence: 95%
“…This recent interest extends beyond auditory access to spectral energy present in phonemes produced with frication noise, such as /s/ and /z/, as in previous years (e.g., Stelmachowicz et al, 2001Stelmachowicz et al, , 2002. Segmental information related to phoneme and sentence recognition (e.g., Donai and Paschall, 2015;Vitela et al, 2015) as well as indexical features of the talker, such as sex (e.g., Monson et al, 2014;Donai and Lass, 2015;Donai and Halbritter, 2017) and talker identity (Schwartz et al, 2018), have also been found in the high-frequency region of the speech signal. Some studies limited auditory access only to high-frequency energy (HFE) above 3-5 kHz (e.g., Donai and Paschall, 2015;Donai and Halbritter, 2017;Monson et al, 2014;Vitela et al, 2015), while others varied the spectral bandwidth of the stimuli to purposely include or exclude HFE above 8 kHz (e.g., Schwartz et al, 2018, Flaherty et al, 2021Polspoel et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Results showed that listeners were able to use information from the high-frequency spectrum to identify speaker gender with accuracy significantly above chance (approximating 90% accuracy). In addition, Donai and Lass 6 recently reported gender recognition abilities among normal-hearing listeners using 250 ms vowel segments high-pass filtered at 3.5 kHz (above F3). Results indicated that normal-hearing listeners were able to identify speaker gender from signals comprised solely of high-frequency energy with greater than 80% accuracy.…”
Section: Introductionmentioning
confidence: 99%